151 SCREENING PRACTICES FOR DIABETIC NEPHROPATHY BASED ON CLINICAL SETTING. Issue 1 (1st January 2007) - Corbett, K.; Egan, B.; Neal, D.; Jenkins, C.
Abstract : Purpose: To perform a cross-sectional study to determine differences in screening, identification, and management of chronic kidney disease in diabetic patients based on clinical setting. Methods: We studied 307 patients with diabetes. These patients were randomly selected from four different clinics, which included two community health centers, an academic endocrine clinic, and an academic primary care clinic. These patients were originally selected for continued quality improvement purposes for the REACH 2010 project in 2005. Annual urine microalbumin and annual serum creatinine were used to determine screening practices. Urine microalbumin > 17 mg/g (men) or > 25 mg/g (women) or GFR < 60 mL/min was used to identify patients with chronic kidney disease. Results: One community health center had a nonsignificant higher proportion of annual urine microalbumins ( p < .074, power = 0.60). One community health center had a significant higher proportion of annual serum creatinines ( p < .0001). In the endocrine clinic, 2 of 4 patients with a positive microalbumin also had a diagnosis of chronic kidney disease, 2 of 20 in the academic primary clinic, 0 of 13 in one community health center, and 2 of 26 in the other community health center. There were very few patients with a positive GFR in either clinic. Conclusion: These findings suggest that community health centers screen patients at higher proportions but are less likely to identify patients who have a positive test.